2009
DOI: 10.1302/0301-620x.91b11.22651
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological outcome of stemmed hip replacement after revision from metal-on-metal resurfacing

Abstract: We report the outcome of total hip replacement in 29 failed metal-on-metal resurfacing hip replacements in which the primary surgery was performed between August 1995 and February 2005. The mean length of follow-up was five years (1.7 to 11.7). Of the 29 hip resurfacings, 19 acetabular components and all the femoral components were revised (28 uncemented stems and one cemented stem). There were no deaths and none of the patients was lost to follow-up. None of the hips underwent any further revision. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
(19 reference statements)
2
20
0
Order By: Relevance
“…They noted no difference in re-revision rates and clinical outcome between the acetabular-sided, femoral-sided, or combined acetabular and femoral-sided (conversion to THA) cohorts, a finding that correlated with the results of the prior study by Su et al [58鈥. Eswaramoorthy et al showed that clinical outcomes in patients undergoing conversion of SRA to THA had clinical results comparable to primary THA, however the clinical scores were significantly worse when compared with patients undergoing primary SRA [65]. Sandiford, in a review of 25 patients undergoing conversion of SRA to THA, found significant postoperative increases in Oxford, Harris, and WOMAC hip scores, with clinical results similar to revision THA [60].…”
Section: Outcomes Of Conversion Of Sra To Thasupporting
confidence: 67%
“…They noted no difference in re-revision rates and clinical outcome between the acetabular-sided, femoral-sided, or combined acetabular and femoral-sided (conversion to THA) cohorts, a finding that correlated with the results of the prior study by Su et al [58鈥. Eswaramoorthy et al showed that clinical outcomes in patients undergoing conversion of SRA to THA had clinical results comparable to primary THA, however the clinical scores were significantly worse when compared with patients undergoing primary SRA [65]. Sandiford, in a review of 25 patients undergoing conversion of SRA to THA, found significant postoperative increases in Oxford, Harris, and WOMAC hip scores, with clinical results similar to revision THA [60].…”
Section: Outcomes Of Conversion Of Sra To Thasupporting
confidence: 67%
“…In both studies a comparison was made with a group of younger patients who had also been treated with resurfacing but without comparison to the current standard of care. Older women are usually regarded 10,9,8,7 for pain, walking, function, and activity, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The conservative nature and stability of hip resurfacing arthroplasty (HRA) make it a viable alternative to conventional total hip arthroplasty (THA) in young and active patients (1,2) because of the preservation of bone mineral density over time in the proximal femur (3)(4)(5)(6)(7) and because of the prospect of potentially easy and successful revision surgery should this be necessary (8)(9)(10)(11). Conventional THA is extremely successful in older patients with hip arthritis and remains the treatment 'gold standard' for this group of patients (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Many surgeons believe resurfacing offers potential benefits [5,9,34], including femoral bone conservation [7], avoidance of stress shielding [21], reduced dislocation rates [17,28], and more revision options [16,27], which are of particular interest when treating young patients. However, systemic metal ion elevation [10] and local adverse reactions [23] continue to cause concern.…”
Section: Introductionmentioning
confidence: 99%